The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15041390
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Treated Alumina and Zirconia Powders Decorated with Hydroxyapatite for Prospective Biomedical Applications

Abstract: The alumina and zirconia surfaces were pretreated with chemical etching using alkaline mixtures of ammonia, hydrogen peroxide and sodium hydroxide, and followed with application of the powder layer of Ca-deficient hydroxyapatite (CDH). The influence of etching bath conditions time and concentration on surface development, chemical composition and morphology of medicinal ceramic powders were studied. The following analyses were performed: morphology (scanning electron microscopy), phase composition (X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Unfortunately, both the mechanical and physical properties of the LSR injection mold fabricated with Al-filled epoxy resins were not better than those fabricated from a conventional steel mold. Thus, enhancing both the mechanical and physical properties of an LSR injection mold by adding some different kinds of reinforcing fillers, such as carbon fibers [ 28 ], zirconia particles [ 29 ], silicon nitride particles [ 30 ], or molybdenum disulfide particles [ 31 ] in Al-filled epoxy resin is also an important research topic. The optimization of the mechanical and physical properties using the Taguchi method for an LSR injection mold could also be investigated [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, both the mechanical and physical properties of the LSR injection mold fabricated with Al-filled epoxy resins were not better than those fabricated from a conventional steel mold. Thus, enhancing both the mechanical and physical properties of an LSR injection mold by adding some different kinds of reinforcing fillers, such as carbon fibers [ 28 ], zirconia particles [ 29 ], silicon nitride particles [ 30 ], or molybdenum disulfide particles [ 31 ] in Al-filled epoxy resin is also an important research topic. The optimization of the mechanical and physical properties using the Taguchi method for an LSR injection mold could also be investigated [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has several intriguing features, such as biocompatibility, biodegradability, osteogenesis, osteoconductivity and bioactivity, and can form direct bonds with living tissues. HAP has many different applications, for example in tissue engineering, nanomedicine, industrial catalysis and in orthopedic implant coating [ 8 , 9 ]. In this last case, it was demonstrated that the use of Ca-deficient hydroxyapatite could favour osseointegration [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…HAP has many different applications, for example in tissue engineering, nanomedicine, industrial catalysis and in orthopedic implant coating [ 8 , 9 ]. In this last case, it was demonstrated that the use of Ca-deficient hydroxyapatite could favour osseointegration [ 9 ]. HAP nano-spheres, thanks to their low solubility in physiological conditions, can be used as carriers for controlled and localized drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Good bone repair materials should not only have a high mechanical strength but also have connected micropore structures similar to those of human bones. Related research results show that porous hydroxyapatite bone repair materials with suitable numbers and sizes of pores can provide growth space for osteoblasts and blood vessels and promote rapid bone growth [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Porous hydroxyapatite bone ceramics have good osteogenic induction properties and enhance the capacity for bone defect repair, which is more in line with the clinical requirements for biological bone repair materials.…”
Section: Introductionmentioning
confidence: 99%